EFEKTIVITAS MEDIA CERITA DIGITAL TERHADAP KETERAMPILAN BERBICARA PESERTA DIDIK DI SEKOLAH DASAR - Munawaroh, Hidayatul; Nuroh, Ermawati Zulikhatin (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to determine the effect of digital storytelling media on elementary students’ speaking skills. The research employed a quantitative approach with a pre-experimental design using a one-group pretest–posttest format. The sample consisted of 23 third-grade students at SDN Sumbersari 1. Data were collected using a speaking skills test administered before and after the treatment. Data analysis included a normality test and a paired sample t-test. The results showed an increase in students’ scores from 72.39 in the pretest to 81.95 in the posttest. Statistical analysis indicated a significance value of 0.001 < 0.05, confirming a significant effect. In conclusion, digital storytelling media is effective in improving students’ speaking skills and can be used as an innovative alternative learning medium in elementary education.